Human Central Auditory Plasticity Associated With Tone Sequence Learning - Gottselig, Julie Marie (Cold Spring Harbor Laboratory Press, 2004)
We investigated learning-related changes in amplitude, scalp topography, and source localization of the mismatch negativity (MMN), a neurophysiological response correlated with auditory discrimination ability. Participants (n = 32) underwent two EEG recordings while they watched silent films and ignored auditory stimuli. Stimuli were a standard (probability = 85%) and two deviant (probability = 7.5% each for high [HD] and low [LD]) eight-tone sequences that differed in the frequency of one tone. Between recordings, subjects practiced discriminating the HD or LD from the standard for 6 min. The amplitude of the LD MMN increased significantly across recordings in both groups, whereas the amplitude of the HD MMN did not. The LD was easier to discriminate than was the HD. Thus, practicing either discrimination increased the MMN for the easier discrimination. Learning and changes in the LD MMN amplitude were highly correlated. Source localizations of event-related potentials (ERPs) to all stimuli revealed bilateral sources in superior temporal regions. Compared with the standard ERP, the LD ERP revealed a stronger source in the left superior temporal region in both recordings, whereas the right-sided source became stronger after learning. Consistent with prior studies of auditory plasticity in animals and humans, tone sequence learning induced rapid neurophysiological plasticity in the human central auditory system. The results also suggest that there is asymmetric hemispheric involvement in tone sequence discrimination learning and that discrimination difficulty influences the time course of learning-related neurophysiological changes.